HUBUNGAN ANTARA KEPUASAN KERJA DENGAN KONFLIK ANTAR KARYAWAN PADA DIVISI REDAKSI PT. X - Amir Hendarsah & Indra Wahyudi (Jurnal Psikologi, 2014)
Fifteen employees who work in an editorial division participated in this research. This is a kind of a surveyed research since the sample size is identical with the population. Objective of this research is verifying the relationship between job satisfaction and conflict awakening among editorial division employees. From this research, the personnel division is expected to design empowerment training toward those employees. It is because source of this research problem is likely the management board of this organization. The dependent variable of this research is conflict, whilst the independent variable is the job satisfaction. Hypothesis of this research is that there is a negative relationship between the job satisfaction and conflict. The more employees satisfy with their job, the lesser their conflict. On the other hand, the less they satisfy with their job the more their conflict awakening. The non- parametric statistic analysis revealed that the rho coefficient is -0.505, p<0.05. The hypothesis is verified. Three research limitations are discussed.